SYNTHESIS AND PROPERTIES OF Ag2O/RGO NANOCOMPOSITE AS CATHODE MATERIALS FOR ZINC - SILVER BATTERIES - Nguyen, Tu Van; Hakim, Shah Abdul (Vietnam Journal of Science and Technology, 2016)
In this article, the effects of Ag2O/reduced graphene oxide (RGO) nanocomposite has been studied by the X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), the field emission scanning electrode microcopy (FESEM) and Raman methods. The discharge/charge property of the Ag2O/RGO nanocomposite was studied by galvanostatic charge-discharge measurement as a cathode material,  CR2032 cells. The results indicated temperature and time for annealing to treated Ag2O/RGO nanocomposite and graphene composition have effect to properties of electrochemical electrode. The Ag2O/RGO nanocomposite electrode may be discharge/charge at hight current density (3 C) and used as a cathode for zinc- silver batteries.